2006
DOI: 10.1029/2005jd006838
|View full text |Cite
|
Sign up to set email alerts
|

Satellite monitoring of the first indirect aerosol effect: Retrieval of the droplet concentration of water clouds

Abstract: [1] A model for the vertical variation of microphysical and optical properties of single-layer water clouds is used to design a procedure to obtain cloud droplet concentration from satellite cloud optical thickness/effective radius retrievals. The model allows for smooth vertical variations in microphysical variables including droplet concentration and liquid water content. The procedure is applied to data from the MODIS instrument aboard the EOS-TERRA satellite platform over a region near Cape Grim, Tasmania,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
106
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(111 citation statements)
references
References 42 publications
4
106
1
Order By: Relevance
“…Opposite to our results, Boers et al (2006) found a clear relation between N CD and N CCN . They, however, studied clouds over the ocean, which do not experience the strong diurnal cycle in atmospheric boundary layer as over land.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Opposite to our results, Boers et al (2006) found a clear relation between N CD and N CCN . They, however, studied clouds over the ocean, which do not experience the strong diurnal cycle in atmospheric boundary layer as over land.…”
Section: Discussioncontrasting
confidence: 55%
“…A way to circumvent this problem is to estimate the cloud droplet number concentration (N CD ), since it directly links cloud optical and microphysical properties to the aerosol concentration at cloud base. Several methods have been developed for this purpose, each one requiring different assumptions about the sub-adiabatic character of and the mixing that occurs inside clouds (Bennartz, 2007;Boers et al, 2006;Szczodrak et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, N i appears as a particularly useful metric to quantify aerosol-cloud interactions due its potentially close link with the aerosol concentration (Kärcher and Ström, 2003;Kay and Wood, 2008;Hendricks et al, 2011). Consequently, while numerous studies have for these reasons used satellite estimates of the cloud droplet number 20 concentration (N d ) to evaluate the indirect aerosol radiative forcing (Boers et al, 2006;Quaas et al, 2006Quaas et al, , 2008Gryspeerdt et al, 2016), the contribution of ice clouds to this effect remains largely unknown (Heyn et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al, 2012;He et al, 2015;Wang et al, 2015;Ban-Weiss et al, 2014). A variety of observational case studies and process studies were also published using similar approaches for deriving CDNC (Boers et al, 2006;George and Wood, 2010;Painemal and Zuidema, 2010;Rausch et al, 2010;. Various authors have addressed shortcomings and issues related to CDNC climatologies (Merk et al, 2016;Grosvenor and Wood, 2014) as well as issues related to the cloud retrievals underlying the CDNC climatologies (Zhang and Platnick, 2011;Nakajima et al, 2010;Maddux et al, 2010;Horvath et al, 2014).…”
Section: Introductionmentioning
confidence: 99%